If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(4r-8)=36-12r
We move all terms to the left:
-3(4r-8)-(36-12r)=0
We add all the numbers together, and all the variables
-3(4r-8)-(-12r+36)=0
We multiply parentheses
-12r-(-12r+36)+24=0
We get rid of parentheses
-12r+12r-36+24=0
We add all the numbers together, and all the variables
-12!=0
There is no solution for this equation
| 6x(-4(x+1))=2x+4 | | −2w=−9 | | 5x+4=99 | | -10+3n=2 | | (17+2x)+23=180 | | n/4-2+4=12 | | 5x−2(x+1)=14 | | -13.92=4+w/7 | | 4-14x=-8+15x | | 3(9-6x)=63 | | 13k+15=54 | | 2k-3(2k-3)=4.5 | | 8x-5=5x+15 | | 2/1(2x-10)=4 | | 8(1+8r)=-8r+8 | | 3/4x-6=-15 | | (m-8)2=0 | | -5/4(9+2x)=40 | | 43v-32=97 | | 7/12x=5/6x-5 | | 10-5x=100 | | -2.2+w/4=-8.6 | | 3.5w+5+5.5w=10w | | 3-2y=-57+10y | | -5-15x=-4x-8x | | 8x-5=5x+15=6x+5 | | 25c+4=49 | | 7(2x-50)-4x=10(51,9-0,1x) | | (6w+4)=2w-10 | | 2x-3-87=180 | | 3=z/5 | | 9y—11=7 |